A Review of Splintered Pieces from Two Lithic Assemblages in Mediterranean Europe: Grotta Della Serratura (Marina di Camerota, Italy) and Cueva de Nerja (Málaga, Spain). (2nd October 2021) - Vadillo Conesa, Margarita; Ricci, Giulia; Bencomo Viala, Mariel; Aura Tortosa, J. Emili; Martini, Fabio
ABSTRACT: The interest of this paper lies in the analysis of variability detected within the group of splintered pieces, establishing distinctions within this broad category. A technological and traceological reading has been used for this purpose. These analyses have been applied to two geographically distant, chronologically disparate assemblages, which make up our case study, Grotta della Serratura, (Italy) and Cueva de Nerja (Spain). Addressing these assemblages together has allowed us to compare the different contexts in which they developed. We have found that the presence of these pieces can be correlated with different points in the chaîne opératoire, knapping, retouch or use; they may all be found at the same site or may be the consequence of a single phase. We have taken these sites as the basis for defining the different categories. This work is therefore intended to be used as a reference for researchers studying lithic assemblages containing such pieces.